Room temperature quantum metric effect in TbMn6Sn6 - Weiyao Zhao; Kaijian Xing; Yufei Zhao; Lei Chen; Min Hong; Yuefeng Yin; Yang Liu; Dang Khoa Le; Jacob Gayles; Fang Tang; Yong Fang; Binghai Yan; et al. (Nature Communications)
Abstract Quantum geometry, including Berry curvature and the quantum metric, of the electronic Bloch bands has been studied via nonlinear responses in topological materials. Naturally, these material systems with intrinsic strong nonlinear responses also form the key component in nonlinear electronic devices. However, the previous reported quantum geometry effects are mainly observed at cryogenic temperatures, hindering their application in practical devices. Here we report a tuneable strong room-temperature second-harmonic transport response in a quantum magnet, TbMn6Sn6, which is governed by the quantum metric and can be tuned with applied magnetic fields. We show that around room temperature, which is close to the spontaneous spin-reorientation transition, the magnetic configurations, and therefore the related symmetry breaking phases, are easily controlled via magnetic fields. Our results also show that manipulation of the symmetries of the magnetic structure presents an effective route to tuneable quantum-geometry-based devices.